2021
DOI: 10.1021/acsami.1c09217
|View full text |Cite
|
Sign up to set email alerts
|

Surface Acoustic Waves to Control Droplet Impact onto Superhydrophobic and Slippery Liquid-Infused Porous Surfaces

Abstract: Superhydrophobic coatings and slippery liquid-infused porous surfaces (SLIPS) have shown their potentials in self-cleaning, anti-icing, antierosion, and antibiofouling applications. Various studies have been done on controlling the droplet impact on such surfaces using passive methods such as modifying the lubricant layer thickness in SLIPS. Despite their effectiveness, passive methods lack on-demand control over the impact dynamics of droplets. This paper introduces a new method to actively control the drople… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 67 publications
(121 reference statements)
0
30
0
Order By: Relevance
“…[11,12] For example, lubrication oil or low freezing point liquids infused with low ice adhesion coating are often damaged mechanically causing the fast run-off of lubricating oil or low freezing point liquids. [13,14] Moreover, the hydrophobic materials-based low ice adhesion coatings are often easily damaged resulting in lost de-icing properties. [15,16] It is believed that to achieve long-time de-icing properties of these low ice adhesion coatings, mechanical durability, and smart function should be integrated into the material, [17,18,19,20,21,22] which are not solved until now.…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] For example, lubrication oil or low freezing point liquids infused with low ice adhesion coating are often damaged mechanically causing the fast run-off of lubricating oil or low freezing point liquids. [13,14] Moreover, the hydrophobic materials-based low ice adhesion coatings are often easily damaged resulting in lost de-icing properties. [15,16] It is believed that to achieve long-time de-icing properties of these low ice adhesion coatings, mechanical durability, and smart function should be integrated into the material, [17,18,19,20,21,22] which are not solved until now.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above background information, Biroun et al 45 reported that there is a large impedance mismatch between the surface of the SAW devices along with the wave propagation and the porous superhydrophobic nanoparticle layer coating (ϕ ≈ 0.57), which results in a wave reflection coefficient of 0.998, calculated using …”
Section: Introductionmentioning
confidence: 99%
“…This low wave reflection coefficient indicates a weak transmission of acoustic energy at the substrate–porous layer interface. Although it is challenging to quantify the porosity of the rime ice layer, we can reasonably assume that the porosity of the rime ice will be higher than that of the nanoparticle porous coating in ref ( 45 ). Therefore, in our case, the SAW acoustic energy will not easily be transmitted through the rime ice layer; thus, the energy will be dissipated significantly into the interfacial layer and the rime ice layer.…”
Section: Introductionmentioning
confidence: 99%
“…A theoretical model is presented that predicts the average initial size of the transferred droplets on the wettable substrates. During these experiments, the wettability of the LiNbO 3 substrate is unaltered since literature 54 suggests that as the wettability of the LiNbO 3 substrate is changed to hydrophobic/superhydrophobic the area fraction through which the surface acoustic waves leak into the droplet decreases and there will be no effect of surface acoustic waves. Finally, the potential application of the technique is demonstrated by transferring streptavidin protein molecules.…”
Section: Introductionmentioning
confidence: 99%